2019
DOI: 10.1093/conphys/coz032
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biological validations of a faecal glucocorticoid metabolite assay in mandrills (Mandrillus sphinx)

Abstract: Stress is a major factor in determining success when releasing endangered species into the wild but is often overlooked. Mandrills (Mandrills sphinx) are vulnerable to extinction due to habitat loss and demand for bush meat and the pet trade. To help bolster in situ populations, rehabilitated rescued mandrills recently were released into a protected area in the Republic of Congo. The goal of this study was to validate the use of faecal glucocorticoid metabolite enzyme immunoassays (EIAs) in mandrills and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 39 publications
(76 reference statements)
0
8
0
Order By: Relevance
“…in other primates (e.g., Bahr et al, 2000;Fichtel et al, 2007;Heistermann et al, 2006;Lavin et al, 2019;Shutt et al, 2012) This study provides information that may be useful to those maintaining this species as a reproductive group in zoos. We provide additional information about the dominance structure of zoo-housed lion-tailed macaques.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…in other primates (e.g., Bahr et al, 2000;Fichtel et al, 2007;Heistermann et al, 2006;Lavin et al, 2019;Shutt et al, 2012) This study provides information that may be useful to those maintaining this species as a reproductive group in zoos. We provide additional information about the dominance structure of zoo-housed lion-tailed macaques.…”
Section: Discussionmentioning
confidence: 97%
“…Due to low CORT values measured here, we also tested and attempted to validate corticosterone, which may be of limited suitability in primates (Bahr et al, 2000; Heistermann et al, 2006), and cortisol metabolite assays 69a and 72t, which have been valuable in other primates (e.g., Bahr et al, 2000; Fichtel et al, 2007; Heistermann et al, 2006; Lavin et al, 2019; Shutt et al, 2012). While corticosterone and 72t did not demonstrate good parallelism to their respective standard curves and measured values were low, it is possible that we needed samples more representative of physiological challenges to validate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of mandrills ( Setchell et al, 2008 ) found no diurnal variation in fGCMs so we collected samples throughout the day. We processed the samples using a validated field-friendly method for hormone extraction in this species ( Lavin et al, 2019 ). We discarded samples contaminated with urine.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, no study has yet examined the stress response during translocation in rehabilitated primates, despite the importance of such studies in informing translocation strategies. We used a previously-validated non-invasive and field-friendly methods to measure fecal glucocorticoid metabolites (fGCMs) in mandrills ( Mandrillus sphinx ) ( Lavin et al, 2019 ) at each stage of a translocation: mandrills housed at the sanctuary, transferred to a pre-release enclosure and released into the forest. fGCMs are a popular physiological biomarker of the stress response, because they can be measured non-invasively and provide an integrated measure of glucocorticoid activity over a period of hours or days, in contrast to the large daily fluctuations in blood saliva or urine samples ( Whitten et al, 1998 ; Hodges and Heistermann, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the cortisol assay showed a higher increase after the stressor with less variation between baseline concentrations [ 96 , 97 ]. However, an EIA against 11β-hydroxyetiocholanolone was the most sensitive to detect stress after a model consisting of routine management in mandrills [ 98 ].…”
Section: Studies Where Total Steroids and Selected Glucocorticoids We...mentioning
confidence: 99%